The Validity and Reliability of the Second Korean Working Conditions Survey - Young Sun Kim; Kyung Yong Rhee; Min Jung Oh; Jungsun Park (Safety and Health at Work, 2013)
Background: The aim of this study was to evaluate the quality of the Second Korean Working Conditions Survey (KWCS), focusing on its validity and reliability. Methods: The external validity was evaluated by the assessment of sampling procedures and the response rate, in order to investigate the representativeness of the sample. The content validity was evaluated by the assessment of the development of the questionnaire, and the consistency of questions for the selected construct. The test-retest method was used to evaluate the reliability by means of a phone call survey of 30% of the respondents, who were randomly selected. The respondents' satisfaction regarding the survey procedures and interview time were analyzed to evaluate the quality of survey data. Results: The external validity was assured by an acceptable sampling procedure, rigid multi-stage stratified cluster random sampling. The content validity was also guaranteed by a reasonable procedure for the development of the questionnaire with a pretest. The internal consistency of the questions for work autonomy was maintained, with 0.738 of Cronbach's alpha. The response rate of 36% was lower than that of the European Working Conditions Survey (EWCS), with a contact rate of 66%, compared to 76% for the EWCS. The matching rates of the five retested questions were more than 98% reliable. Conclusion: The quality of the second KWCS was assured by the high external and content validity and reliability. The rigid sampling procedure and development of the questionnaire contributed to quality assurance. The high level of reliability may be guaranteed by the sophisticated field survey procedures and the development of a technical manual for interviewers. The technical strategies for a high response rate should be developed for future surveys.